The Association between Advanced Maternal Age and Diagnosis of Small for Gestational Age - Palatnik, Anna; De Cicco, Sarah; Zhang, Liyun; Simpson, Pippa; Hibbard, Judith; Egede, Leonard E. (American Journal of Perinatology, 2020)
Objectives To identify whether advanced maternal age (AMA), defined as age ≥35 years old, is independently associated with small for gestational age (SGA).Study Design This was a retrospective cohort of births from the National Vital Statistics System in the United States from 2009 to 2013. Women were categorized based on four age groups at the time of delivery: 20 to 29, 30 to 34, 35 to 39, and ≥40 years old. The primary outcome of SGA < 10th and SGA < 5th percentiles was compared between the four groups using both univariable and multivariable analyses to determine whether maternal age was associated with SGA independent of parity.Results A total of 17,031,005 births were eligible for analysis, with 2,705,501 births to AMA women. In multivariable analyses, maternal age of 30 to 34, compared with 20 to 29, was associated with lower rates of SGA < 10th and <5th percentiles (adjusted odds ratio [aOR] = 0.95; 95% confidence interval [CI]: 0.95–0.96 and aOR = 0.97; 95% CI: 0.96–0.98, respectively). The AMA of 35 to 39, compared with 20 to 29, was associated with lower rates of SGA < 10th percentile and unchanged rates of SGA < 5th percentile (aOR = 0.97; 95% CI: 0.96–0.98 and aOR = 1; 95% CI: 0.99–1.01, respectively). In contrast, AMA of ≥40, compared with age 20 to 29, was associated with higher rates of both SGA < 10th and <5th percentiles (aOR = 1.06; 95% CI: 1.04–1.07 and aOR = 1.14; 95% CI: 1.12–1.16, respectively). A significant association was found between maternal age and parity toward the risk of SGA (p < 0.001). Nulliparous women ≥30 years old but not multiparous women had higher rates of SGA < 10th and SGA < 5th percentiles compared with nulliparous women in the age group of 20 to 29. In contrast, both nulliparous and multiparous women age ≥40 years old had an increased risk for SGA < 5th percentile compared with all women in the age group of 20 to 29.Conclusion Nulliparous women aged 30 years and older have higher risk of SGA < 10th and SGA < 5th percentiles compared with nulliparous women age 20 to 29. In contrast, both nulliparous and multiparous women age 40 years and older have an increased risk of SGA < 5th percentile compared with all women in the age group of 20 to 29.
Keywords: advanced maternal age; small for gestational age; parity; paternal age